2013
DOI: 10.36953/ecj.2013.14304
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor SPM in kitchens of household using different modes of cooking in Jammu, India

Abstract: The present study has been carried out to assess indoor SPM levels in kitchens of the household using different modes of cooking in Jammu using handy air sampler (Envirotech APM 821) with air flow rate of 1.5 LPM from 6am to 2pm. All the kitchens with different modes of cooking exhibited values of indoor SPM higher than the prescribed CPCB values of 200 µg/m3. Complied average values of SPM were used to calculate IPI (Indoor Pollution Index). The calculated values of indoor SPM in all the four types of kitchen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Households with LPGinduction as cooking fuel and Modular Kitchen revealed PM1.0 and PM0.50 exhibited the trend Drawing room followed by Bedroom and lowest in the Kitchen whereas PM2.5 exhibited the trend Bedroom followed by Drawing room and lowest in the Kitchen and PM0.25 exhibited the trend Drawing room followed by Kitchen and lowest in the Bedroom in the overall study area (Table 6). Rampal and Chib (2013) while studying indoor suspended particulate matter (SPM) levels in kitchens of households using various cooking methods noticed that SPM levels were higher than the levels prescribed by CPCB (200 µg/m³) in all households. They also found that fuelwood using kitchens had the highest SPM (1435.54 ± 849.47µg/m³), followed by kitchens using kerosene oil (710.06 ± 180.37µg/m³), kitchens using LPG (376.79 ±140.98µg/m³) and kitchens using electric heater (262.08 ± 95.90µg/m³) as their mode of cooking.…”
Section: Resultsmentioning
confidence: 99%
“…Households with LPGinduction as cooking fuel and Modular Kitchen revealed PM1.0 and PM0.50 exhibited the trend Drawing room followed by Bedroom and lowest in the Kitchen whereas PM2.5 exhibited the trend Bedroom followed by Drawing room and lowest in the Kitchen and PM0.25 exhibited the trend Drawing room followed by Kitchen and lowest in the Bedroom in the overall study area (Table 6). Rampal and Chib (2013) while studying indoor suspended particulate matter (SPM) levels in kitchens of households using various cooking methods noticed that SPM levels were higher than the levels prescribed by CPCB (200 µg/m³) in all households. They also found that fuelwood using kitchens had the highest SPM (1435.54 ± 849.47µg/m³), followed by kitchens using kerosene oil (710.06 ± 180.37µg/m³), kitchens using LPG (376.79 ±140.98µg/m³) and kitchens using electric heater (262.08 ± 95.90µg/m³) as their mode of cooking.…”
Section: Resultsmentioning
confidence: 99%